(untitled) (Hematology Meeting Reports, 2009)
Circulating human γδ T lymphocytes comprise a unique lymphoid cell subset exerting strong cytolytic activity against cancer cells.1 In healthy adults, around 1% of peripheral blood mononuclear cells are gd T lymphocytes, most of which harbour a CD3+ CD4– CD8– NKG2D+ phenotype and express the same TCR Vγ9/dδ2 gene-encoded receptor for antigens. These lymphocytes often referred to as Vγ9/V2δ+ T cells do respond to both human cancer cells and tuberculosis infection, by the selective recognition of HLA-unrestricted antigens with non-peptide phosphoesters structures, the phosphoantigens.2